2010
DOI: 10.1364/ao.49.005736
|View full text |Cite
|
Sign up to set email alerts
|

Loose abrasive slurries for optical glass lapping

Abstract: Loose abrasive lapping is widely used to prepare optical glass before its final polishing. We carried out a comparison of 20 different slurries from four different vendors. Slurry particle sizes and morphologies were measured. Fused silica samples were lapped with these different slurries on a single side polishing machine and characterized in terms of surface roughness and depth of subsurface damage (SSD). Effects of load, rotation speed, and slurry concentration during lapping on roughness, material removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 16 publications
1
22
1
1
Order By: Relevance
“…Ponadto płaskość narzędzia odwzorowywana jest na powierzchni przedmiotu obrabianego [7]. W obróbce ściernej ważna jest również zawiesina ścierna -jej stężenie i objętość oraz rodzaj i wielkość ziaren [8]. Znaczenie mają także geometria i materiał przedmiotów obrabianych.…”
Section: Parametry Docierania 1-tarczowegounclassified
“…Ponadto płaskość narzędzia odwzorowywana jest na powierzchni przedmiotu obrabianego [7]. W obróbce ściernej ważna jest również zawiesina ścierna -jej stężenie i objętość oraz rodzaj i wielkość ziaren [8]. Znaczenie mają także geometria i materiał przedmiotów obrabianych.…”
Section: Parametry Docierania 1-tarczowegounclassified
“…In addition, the flatness, geometric and arrangement of workpieces have also effect on lapping results. The material hardness of workpieces has a crucial influence on a removal mechanism in abrasive processes, as well on efficient of lapping [9]. Surface formation of fragile workpieces, e.g., ceramics, occurs as a result of cracking propagation or by plastic deformation, when depth of cut is smaller than critical [10].…”
Section: Main Factors Of Lapping Processmentioning
confidence: 99%
“…Material studied Grinding type Abrasive Grinding mode Influence on SSD Agarwal et al [6] SiC Rough Bound b ap ⇒ SSD Perveen et al [7] BK7 glass Micro Bound b ap ⇒ SSD Esmaeilzare et al [8] Zerodur glass Rough Bound b Vc ⇒ SSD Maksond et al [9] Si3N4 Rough Bound c ap ⇒ SSD Li et al [10] Fused silica Rough to finish Bound c ap ⇒ SSD Pei et al [5] Si wafers Fine Bound a Vc, f no influence Wang et al [11] BK7 glass Polishing Loose a Ca ⇒ SSD Zhang et al [12] Nd doped phosphate glass Polishing Loose a Vc ⇒ SSD Neauport et al [13] Fused silica Polishing Loose a Vc, Ca, P ⇒ SSD…”
Section: Authorsmentioning
confidence: 99%
“…The grinding wheel rotation and workpiece are parallel and the feed direction is perpendicular to this direction (a). The grinding wheel rotation and the feed direction are parallel to the workpiece (b).The feed direction is parallel to the workpiece and the grinding wheel rotation is perpendicular (c) SSD depth in neodymium-doped phosphate glass decreases when the spindle speed increases [12], and Neauport et al found that SSD depth in fused silica decreases when the spindle speed, the load and the abrasive concentration increase [13].…”
Section: Introductionmentioning
confidence: 99%